The essential patient handbook : getting the health care you need-- from doctors who know - Ettinger, Alan B. (Demos Medical Pub., 2004)
The Essential Patient Handbook was written for the millions of Americans who are dissatisfied with their medical care, and are looking for a practical no-nonsense way to get the help they need from their doctors. It contains lessons learned by two doctors (husband and wife) who endured immense challenges on the patient side of the medical care system. Here are the secrets to: getting your doctor to listen; preparing information your doctor needs to know; understanding the reasoning behind your doctor's questions; asking the essential questions about tests, diagnoses, medications, surgery, and.